Hubungan Perilaku Makan dan Body Image dengan Status Gizi Remaja Putri di SMA Negeri 13 Bone - Leni Leni; Sakinah Amir; Hasnidar Hasnidar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Adolescent girls face nutritional challenges due to rapid physical, psychological, and social changes, with eating behavior and body image playing crucial roles in determining nutritional status. This study aimed to analyze the relationship between eating behavior and body image with nutritional status among female students at SMA Negeri 13 Bone. A quantitative cross-sectional design was employed, involving 60 respondents selected through proportionate stratified random sampling from a population of 495 students. Data were collected using the Dutch Eating Behavior Questionnaire (DEBQ), Body Shape Questionnaire (BSQ), and anthropometric measurements for Body Mass Index (BMI). Descriptive and inferential analyses, including Spearman correlation and ordinal regression, were conducted using SPSS. The results showed a significant positive relationship between eating behavior and nutritional status, as well as between body image and nutritional status. Most respondents had normal nutritional status, but some experienced undernutrition, overnutrition, or obesity. The study concludes that both eating behavior and body image are important determinants of nutritional status in adolescent girls, highlighting the need for integrated nutrition education and body image interventions in schools